2020
DOI: 10.3168/jds.2020-18564
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of differentially expressed whey proteins in Guanzhong goat milk and Holstein cow milk by iTRAQ coupled with liquid chromatography-tandem mass spectrometry

Abstract: Guanzhong goat and Holstein cow milk are the major milks supplied in China. Whey proteins play an important role in immune defense for newborn mammals. This study aimed to analyze the differentially expressed whey proteins of Guanzhong goat milk and Holstein cow milk by using isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomics techniques. A total of 165 whey proteins were quantified, 114 of which differed significantly in abundance in goat and cow milks. According to the "up_keywords,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Serpin A3–1, an inhibitor of the serine proteases elastase and trypsin, has been detected in bovine milk. A previous study using an iTRAQ-LC-MS quantification–based proteomics approach showed that serpin A3–1 abundance was significantly higher in bovine milk than in goat milk ( Sun, Wang, Sun, & Guo, 2020 ). In the current study, serpin A3–1 was present in goat milk adulterated with bovine milk and could be used to assess such adulteration of goat milk samples.…”
Section: Discussionmentioning
confidence: 99%
“…Serpin A3–1, an inhibitor of the serine proteases elastase and trypsin, has been detected in bovine milk. A previous study using an iTRAQ-LC-MS quantification–based proteomics approach showed that serpin A3–1 abundance was significantly higher in bovine milk than in goat milk ( Sun, Wang, Sun, & Guo, 2020 ). In the current study, serpin A3–1 was present in goat milk adulterated with bovine milk and could be used to assess such adulteration of goat milk samples.…”
Section: Discussionmentioning
confidence: 99%